Persistent Effects of Developmental Exposure to 17α-Ethinylestradiol on the Zebrafish (Danio rerio) Brain Transcriptome and Behavior - Porseryd, Tove; Volkova, Kristina; Reyhanian Caspillo, Nasim; Källman, Thomas; Dinnetz, Patrik; Porsh Hällström, Inger (Frontiers in Behavioral Neuroscience, 2017)
The synthetic estrogen 17α-ethinylestradiol (EE2) is an endocrine disrupting compound of concern due to its persistence and widespread presence in the aquatic environment. Effects of developmental exposure to low concentrations of EE2 in fish on reproduction and behavior not only persisted to adulthood, but have also been observed to be transmitted to several generations of unexposed progeny. To investigate the possible biological mechanisms of the persistent anxiogenic phenotype, we exposed zebrafish embryos for 80 days post fertilization to 0, 3 and 10 ng/L EE2 (measured concentrations 2.14 and 7.34 ng/L). After discontinued exposure, the animals were allowed to recover for 120 days in clean water. Adult males and females were later tested for changes in stress response and shoal cohesion, and whole-brain gene expression was analyzed with RNA sequencing. The results show increased anxiety in the novel tank and scototaxis tests, and increased shoal cohesion in fish exposed during development to EE2. RNA sequencing revealed 34 coding genes differentially expressed in male brains and 62 in female brains as a result of EE2 exposure. Several differences were observed between males and females in differential gene expression, with only one gene, sv2b, coding for a synaptic vesicle protein, that was affected by EE2 in both sexes. Functional analyses showed that in female brains, EE2 had significant effects on pathways connected to the circadian rhythm, cytoskeleton and motor proteins and synaptic proteins. A large number of non-coding sequences including 19 novel miRNAs were also differentially expressed in the female brain. The largest treatment effect in male brains was observed in pathways related to cholesterol biosynthesis and synaptic proteins. Circadian rhythm and cholesterol biosynthesis, previously implicated in anxiety behavior, might represent possible candidate pathways connecting the transcriptome changes to the alterations to behavior. Further the observed alteration in expression of genes involved in synaptogenesis and synaptic function may be important for the developmental modulations resulting in an anxiety phenotype. This study represents an initial survey of the fish brain transcriptome by RNA sequencing after long-term recovery from developmental exposure to an estrogenic compound.